THE PROCESS OF CHARACTER EDUCATION IN THE PERSPECTIVE OF ISLAMIC EDUCATION - Supala, Supala (Journal of Islamicate Studies, 2019)
This paper discusses the process of character education. By using a literature survey, this paper found that to be able to form students have strong character, serious and certain steps are needed, becouse of strengthening character education is a very important effort to achieve national education goals. Character education must be instilled from an early age and will be the main foundation for the formation of national character. Given the importance of character education, educators must make efforts to introduce and develop character education for students. One form of effort to strengthen the character of students in school is through ways of habituating noble character. The aim of Islamic education must be to return to basic values (back to basic), namely the Qur'an and Al-Hadith as pure sources. Therefore, if humans are predicated on Muslims, they will truly be adherents of a good religion, obeying the teachings of Islam and keeping God's grace in them. He must be able to understand, appreciate, and practice his teachings according to the faith and Islamic faith. For this purpose, humans must be educated through the process of Islamic education.